The Role of Heritage Image as an Intervening Factor in Increasing Visits to Lawang Sewu - Dina, Novia Rahma; Firdaus; Purwanto, Edy; Jumai (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
This research seeks to assess the impact of service quality and destination branding on the decision to visit the Lawang Sewu Semarang tourist attraction, which are mediated by heritage images. KAI Wisata, as the manager of Lawang Sewu, is targeting 700 thousand tourists in 2024. However, until December 31, 2024, the number of foreign and domestic tourists visiting the area for one year reached 650 thousand visitors. This is actually good, but not yet in accordance with the target set. This research used quantitative methods on 96 respondents. Therefore, the data analysis is performed using SmartPLS. The research results show that service quality and destination branding are proven to increase visiting decisions. Decisions to visit are positively and significantly influenced by service quality, destination branding, and heritage image. This can provide insight into increasing public interest in the Lawang Sewu tourist attraction.